TAKDİR KOMİSYONLARININ TÜRK İDARİ TEŞKİLATI VE TÜRK VERGİ HUKUKU İÇİNDEKİ YERİNİ VE İŞLEVİNİ SAPTAMA DENEMESİ: DEMOKRATİK VE İYİ İDARE ANLAYIŞI BAĞLAMINDA BİR DEĞERLENDİRME - (:unkn) unknown (My University, 2020)
Çağdaş vergi sistemlerinde vergi matrahının tespitinde egemenolan usûl, beyana dayalı gerçek usuldür. Bu usûle göre vergi matrahı,kanunlarda belirlenen vergi doğurucu olayların meydana gelmesi üzerine, yine kanunlarda belirlenen esaslara göre tespit edilir. Tarihi süreçiçinde, beyana dayalı gerçek usul, geleneksel matrah tespit yöntemlerinden biri olarak adlandırabileceğimiz götürü usulün kullanım alanını zamanla daraltarak; egemenlik kazanmıştır. Beyana dayalı sistemde gerçekmatrahların veya matrahı etkileyen unsurların mükelleflerce tespitimümkün olmadığında, matrah tespit görevi, re’sen takdir yöntemi kullanılmak üzere İdare’ye geçmektedir. Bu durumda amaç gerçek matrahıbulmak, bu mümkün olamıyorsa da gerçeğe en yakın matrahı tespit et-mektir. Matrahın veya matrahı etkileyen unsurların re’sen takdir yoluylabulunmasında, kanun koyucu yetkiyi İdare memurlarından ve mükelleftemsilcilerinden oluşan karma yapılı takdir komisyonlarına bırakmıştır.Kanun koyucu, matrah takdirinde mükellef temsilcilerini de sürece katarak bütün yetkiyi İdare’ye bırakmamış; bu sayede de hem mükellef haklarını gözetmiş hem de demokratik (iyi) idare ilkesini somutlaştırmıştır.Her ne kadar tarihi süreç içinde takdir komisyonlarının işlevi azalsa da;bu komisyonların varlığı demokratik (iyi) idare anlayışı açısından yaşamsal değerdedir. Bu çalışmada takdir komisyonlarının vergi ve idarehukukundaki yeri ve işlevi saptanarak; karma yapılı bu komisyonlarınvarlığının değeri, demokratik (iyi) idare anlayışı çerçevesinde irdelenmiştir.

The declaration-based real tax system is the dominant method in the determination of tax base in modern tax systems. In this method, following the occurance of the taxable event provided by law, the tax base is determined according to the principles which were also provided by law. The declaration-based real tax system became dominant by narrowing the scope of lump-sum system that we may describe as one of the traditional methods for the determination of tax base. When it's impossible to determine the tax base or the elements that affect this base, the assessment task, this time to be exercised in an ex-officio manner, is transferred to the Administration. In this case, the purpose is to find out the real tax base, or, if it's not likely, the base that’s closest to the real one. The law entitles the mixed valuation commissions, consisting of Administration officers and taxpayer representatives, to determine the tax base or the elements that affect this base. By including the taxpayer representatives in the process, the legislator did not leave all the power to the administration, and thus, it paid regard to the rights of the taxpayers and also realise the democratic (good) administration perspective. Although the functions of these valuation commissions diminished in time, their existence is crucial in terms of the democratic (good) administration perspective. In this study, the place and functions of the valuation commissions in the administrative law and the tax law are determined, and the significance of these mixed commissions are examined within the frame of the democratic (good) administration perspective.
AN ESSAY ON DETERMINING THE PLACE AND FUNCTIONS OF VALUATION COMMISSIONS IN TURKISH ADMINISTRATIVE ORGANIZATION AND TAX LAW: AN EVALUATION WITHIN THE CONTEXT OF DEMOCRATIC AND GOOD ADMINISTRATION PERSPECTIVE